ANT goes dispositif: Überlegungen zu einer methodischen Verschränkung von Akteur-Netzwerk-Theorie und Dispositivanalyse. Issue 1 (5th July 2018) - Gnosa, Tanja
This article examines methodological problems in Foucault's dispositif analysis and Latour's actor-network theory. In order to address the question of the two methods' compatibility, the paper does not start from Foucault's dispositif, but from discourse theory. It is argued that the former is grounded in the latter, and that Latour's ANT — both in its initial as well as in its recent form (as formulated in the Modes of Existence ) — is based on an underlying and implicit Foucauldian discourse logic. In a second step, the dispositif analysis is introduced on the basis of what could be called Foucault's problem, i.e., the question of how to categorize dispositifs . The article shows that ANT has a similar problem that Latour tries to solve by introducing his modes of existence . A combined reading of the two approaches, the author finally states, can very fruitfully contribute to cultural analysis.